Preliminary Phytochemical Screening of Aqueous Extract of Ficus Bengalensis Leaf Bud (AYUSHDHARA, 2023)
Biologically active compounds present in plants are called phytochemicals. Phytochemicals are produced by plants as part of their defense mechanisms against various stresses, such as pathogens, predators, or environmental factors. These can be derived from barks, leaves, flowers, roots, fruits and a seed, knowledge of the chemical constituents of plants is desirable because they are used as direct sources of medicinal agent and such information will be valuable for synthesis of complex chemical substances. Vata (Ficus bengalensis) is such a herbal drug which is widely available and is having many mentioning in the classics for its effectiveness in Stree Vandhyatwa. Its vegetative buds are used in the treatment of Vandhyatwa. This paper mainly deals with the collection of leaf bud of Ficus bengalensis, and qualitative screening of the aqueous extract for the available phytochemicals. The extract of leaf bud was tested for the presence of tannins, flavonoids, phenols, glycosides, proteins, saponins and steroids by using standard protocols.